Rehabilitation of a Child with Denari Prosthesis after Dental Avulsion - César Sebastián Arcos-López; Juan Marcos Parise-Vasco; Ana Armas-Vega; Yecenia Carrillo-Azuero (Case Reports in Dentistry)
Prosthetic rehabilitation in cases of premature loss of temporary teeth always is a procedure that must be carried out in a planned and integral manner. The avoidance of opposing tooth extrusion, loss of horizontal space, and acquisition of bad oral habits are fundamental to not trigger alterations in the child’s occlusal development and psychological development. The purpose of this document is to report the clinical case of a 4-year-old patient with avulsion of the anterior primary teeth secondary to severe automobile trauma. In this case, we describe the use of a Denari-type fixed partial prosthesis. This prosthesis can recover the function and aesthetics of the superior anterior sector of the oral cavity, thus preventing lingual interposition. The treatment with the Denari prosthesis allowed satisfactory results relating to the transverse growth of the maxillary bone in this case report.